Job Insecurity and Mental Health: The Moderating Role of Coping Strategies From a Gender Perspective - Menéndez-Espina, Sara; Llosa, Jose Antonio; Agulló-Tomás, Esteban; Rodríguez-Suárez, Julio; Sáiz-Villar, Rosana; Lahseras-Díez, Héctor Félix (Frontiers in Psychology, 2019)
Job insecurity is a growing phenomenon, typical of an employment context characterised by high rates of temporary work and unemployment. Previous research has shown a direct relationship between job insecurity and mental health impairment. The present analysis goes into this relationship in depth, studying the moderating role of coping strategies and predicting that men and women implement different types of strategies. A sample of 1.008 workers is analysed, 588 women and 420 men. The Tobin CSI scale was used to analyse the coping strategies, in addition to JIS-8 to assess job insecurity, the MOS Perceived Social Support Survey and the GHQ-28 test to evaluate mental health. Then, a hierarchical linear regression was designed to study the moderating role of 8 coping strategies of job insecurity and 4 mental health subscales in men and women, separately. Results illustrate that coping strategies play a moderating role in the relationship between job insecurity and mental health. However, the aggravating role of disengagement coping strategies is more relevant than the buffering role of engagement strategies. On the other hand, women implement a greater number of coping strategies, with more positive results for mental health. Also, in the relationship between job insecurity and mental health the most important strategies are the ones related to social interaction inside and outside an organisation, and these are the main ones used by women. It therefore follows that strengthening rich social relationships inside and outside the working environment is a guarantee of well-being.